A Developmental Role of the Cystic Fibrosis Transmembrane Conductance Regulator in Cystic Fibrosis Lung Disease Pathogenesis - Huang, Elena N.; Quach, Henry; Lee, Jin-A; Dierolf, Joshua; Moraes, Theo J.; Wong, Amy P. (Frontiers in Cell and Developmental Biology, 2021)
The cystic fibrosis (CF) transmembrane conductance regulator (CFTR) protein is a cAMP-activated anion channel that is critical for regulating fluid and ion transport across the epithelium. This process is disrupted in CF epithelia, and patients harbouring CF-causing mutations experience reduced lung function as a result, associated with the increased rate of mortality. Much progress has been made in CF research leading to treatments that improve CFTR function, including small molecule modulators. However, clinical outcomes are not necessarily mutation-specific as individuals harboring the same genetic mutation may present with varying disease manifestations and responses to therapy. This suggests that the CFTR protein may have alternative functions that remain under-appreciated and yet can impact disease. In this mini review, we highlight some notable research implicating an important role of CFTR protein during early lung development and how mutant CFTR proteins may impact CF airway disease pathogenesis. We also discuss recent novel cell and animal models that can now be used to identify a developmental cause of CF lung disease.